2014
DOI: 10.1371/journal.pone.0106865
|View full text |Cite
|
Sign up to set email alerts
|

Soil Mineral Composition Matters: Response of Microbial Communities to Phenanthrene and Plant Litter Addition in Long-Term Matured Artificial Soils

Abstract: The fate of polycyclic aromatic hydrocarbons (PAHs) in soil is determined by a suite of biotic and abiotic factors, and disentangling their role in the complex soil interaction network remains challenging. Here, we investigate the influence of soil composition on the microbial community structure and its response to the spiked model PAH compound phenanthrene and plant litter. We used long-term matured artificial soils differing in type of clay mineral (illite, montmorillonite) and presence of charcoal or ferri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Our finding of a selective colonization of typical soil minerals encompassing species specific and predictable successional patterns has implications for the biogeochemical genesis, transformation and stability of the organo-mineral complexes. Clay minerals and iron oxyhydroxides affect biogeochemical processes through selective adsorption and protection of soil organic matter (Heckman et al, 2012), inactivation of extracellular enzymes, formation of organometal complexes (Finley et al, 2018) and provide opportunities for soil restoration and CO 2 mitigation (Baer et al, 2010;Babin et al, 2014). Moreover, physiological and biochemical differences between consecutive bacterial colonizers likely influence geochemical changes on mineral surfaces like weathering and aggregate formation (Lepleux et al, 2012;Ahmed and Holmström, 2015;Costa et al, 2018), the transformation and formation of organomineral complexes, and the accumulation of microbially derived soil organic matter (Kallenbach et al, 2016).…”
Section: Implications For Soil Microbiology and Biogeochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of a selective colonization of typical soil minerals encompassing species specific and predictable successional patterns has implications for the biogeochemical genesis, transformation and stability of the organo-mineral complexes. Clay minerals and iron oxyhydroxides affect biogeochemical processes through selective adsorption and protection of soil organic matter (Heckman et al, 2012), inactivation of extracellular enzymes, formation of organometal complexes (Finley et al, 2018) and provide opportunities for soil restoration and CO 2 mitigation (Baer et al, 2010;Babin et al, 2014). Moreover, physiological and biochemical differences between consecutive bacterial colonizers likely influence geochemical changes on mineral surfaces like weathering and aggregate formation (Lepleux et al, 2012;Ahmed and Holmström, 2015;Costa et al, 2018), the transformation and formation of organomineral complexes, and the accumulation of microbially derived soil organic matter (Kallenbach et al, 2016).…”
Section: Implications For Soil Microbiology and Biogeochemistrymentioning
confidence: 99%
“…It is unclear to which extent colonization involves different types of microbial communities and consecutive replacement. Some studies have either investigated adhesion of single bacterial species to individual minerals in laboratory cultures (Chenu and Stotzky, 2002;Hong et al, 2012;Huang et al, 2015;Ahmed et al, 2017) or bacterial colonization of artificial soils incubated in laboratory microcosms (Heckman et al, 2012;Pronk et al, 2012;Ding et al, 2013;Babin et al, 2014;Hemkemeyer et al, 2014;Ditterich et al, 2016). The latter demonstrated that microbial communities changed over relatively short time spans of 6 to 18 months (Heckman et al, 2012;Hemkemeyer et al, 2014;Ditterich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the communities responded differently to the spiking of organic amendments Babin et al 2013Babin et al , 2014Pronk et al 2017). This suggests that expandable layer silicate minerals might therefore influence the effects of QAACs in soil not only by sequestration of the compound (Fig.…”
Section: Effects Of Qaacs On the Soil Microbial Communitymentioning
confidence: 99%
“…Only recently it has been recognized that graphite might be utilized by soil microbes (Liu et al, 2015;Hemingway et al, 2018), but little is known about the exact role of graphite on overall soil microbial life. As stated in previous publications (e.g., Ding et al, 2013;Babin et al, 2014;Fierer, 2017), factors affecting prokaryotic community composition in soil can be manifold. For now, we can therefore not exclude an effect of other parameters on the prokaryotic community that were not taken into account in this study.…”
Section: Microaggregation and Microaggregate Stability As Explained Bmentioning
confidence: 91%
“…Mineral composition of the soil controlled by the parent material, has an important impact on soil aggregation and the microbial community assemblage, and how it responds to OM inputs by e.g., promoting or inhibiting growth of particular microbial taxa (Babin et al, 2014). For instance, carbonates affect soil pH and have therefore distinct effects on the soil microbiome (Fierer, 2017).…”
Section: Introductionmentioning
confidence: 99%